2006
DOI: 10.1007/s10886-005-9006-7
|View full text |Cite
|
Sign up to set email alerts
|

A New Potential Attractant for Anastrepha obliqua from Spondias mombin Fruits

Abstract: Nonirradiated males and females of Anastrepha obliqua (Macquart) were attracted to and landed more frequently on ripe fruits of Spondias mombin L. than on artificial fruit in wind tunnel bioassays. Porapak Q volatile extracts of S. mombin were also attractive and elicited landing on artificial fruit for both sexes. Combined gas chromatographic-electroantennographic detection (GC-EAD) analysis of volatile extracts showed that nine volatile compounds elicited repeatable antennal responses from females and males.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 30 publications
0
51
0
2
Order By: Relevance
“…Males and females of A. ludens were signiÞcantly more attracted to guava, Psidium guajava L., fruit, landing more on these fruit than on control yellow spheres (Malo et al 2005). Cruz-Ló pez et al (2006) in a Þeld cages, found that a fruit volatile blend from Spondias mombin L. were more attractive to fruit ßies than hydrolyzed protein. The blend of components isolated from white sapote fruit attractive to A. ludens in this study was different to the attractive blend from yellow chapote S. greguii, termed CEHO (1,8-cineole, ethyl butyrate, 1-hexanol, and ethyl octanoate) (Robacker et al 1992), except that 1,8-cineole was present in both blends.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Males and females of A. ludens were signiÞcantly more attracted to guava, Psidium guajava L., fruit, landing more on these fruit than on control yellow spheres (Malo et al 2005). Cruz-Ló pez et al (2006) in a Þeld cages, found that a fruit volatile blend from Spondias mombin L. were more attractive to fruit ßies than hydrolyzed protein. The blend of components isolated from white sapote fruit attractive to A. ludens in this study was different to the attractive blend from yellow chapote S. greguii, termed CEHO (1,8-cineole, ethyl butyrate, 1-hexanol, and ethyl octanoate) (Robacker et al 1992), except that 1,8-cineole was present in both blends.…”
Section: Discussionmentioning
confidence: 98%
“…Fruit volatiles were collected using a technique described previously (Cruz-Ló pez et al 2006). A charcoal-Þltered airstream (1 liter/min) was maintained through a cylindrical glass aeration chamber (58 cm in length by 18.5 cm i.d.)…”
Section: Methodsmentioning
confidence: 99%
“…Some animal species utilize ethyl benzoate in their chemical communication system. For example, it is part of the pheromone mix of the interdigital gland of male white-tailed deer (Gassett et al, 1996) and it is an attractant for some tephritids like the oriental fruit fly Bactrocera dorsalis and the West Indian fruit fly Anastrepha oblique (Chu et al, 1996;Cruz-López et al, 2006). While ethyl benzoate is not a common volatile of leaves, it was produced by apple leaves after infestation by the spider mite Tetranychus urticae (Takabayashi et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…P. mali than by healthy apple plants. Ethyl benzoate is capable of eliciting reactions from insects of other genera (Chu et al, 1996;Cruz-López et al, 2006;Beck et al, 2011) but to confirm whether psyllids, especially C. picta, recognize and are responsive to it will require that additional EAG (electroantennography) and olfactometer experiments are performed.…”
Section: Discussionmentioning
confidence: 99%
“…Each trap contained 250 mL of water, and 2 mL of Tween 80 (ICI, Wilmington, DE), which were added to retain flies, while others traps were baited with 10 mL of the hydrolyzed protein mixed with 5 g of borax dissolved in 235 mL of water per trap. The synthetic blend of S. mombin fruits were prepared as described elsewhere (Cruz-López et al 2006), and 100 μL of synthetic blend were loaded in a rubber septum (Sigma-Aldrich, Toluca, Mexico). The rubber septa were put in the lure compartment of the Multilure trap.…”
mentioning
confidence: 99%